New insights into the depositional facies of the Early Eocene Rus Formation, Bahrain - Amer Aimen; Skyttä Pietari; Ojala Antti; Heilimo Esa (Elsevier Ltd, 2025)
Detailed geological field measurements combined with petrographic and mineralogical analyses of the Horse Racing Club outcrop, Bahrain, revealed new insights into the composition, facies distribution, and depositional settings of the Early Eocene Rus Formation, which is poorly constrained in Bahrain. The mineralogical analysis revealed that the rock-forming units are dominated by dolomite, dolomitic marl, claystone, and minor evaporites. The integration of field data and lab measurements resulted in the identification of thirteen facies that are grouped into five facies associations comprising i) lagoonal complexes, ii) sabkha complexes, iii) transgressive lag, iv) peritidal channel complexes, and v) barrier island and washover complexes. Combined paleocurrent analysis of field-observed clinoformal structures, lateral accretion surfaces, and trough cross-bedding indicate a NNW–SSE paleoshoreline trend with tidal channels trending dominantly towards NE–SW and NW–SE directions. The depositional facies model developed for the Rus Formation in Bahrain and within the surrounding region suggests that during the Early Eocene, two landmasses existed to the north and south of Bahrain, restricting the Neo-Tethys Ocean flow through a relatively narrow strait that was influenced by periodic storms. The results of this paper challenge the role of the Rus Formation as an effective regional hydrocarbon seal and, as such, highlight the need for a critical evaluation of the associated petroleum system potential in Bahrain and neighboring countries.